Measuring success: a school-university partnership model for widening participation in higher education - Bray, Aibhin (My University, 2025)
This paper investigates the impact of a widening participation outreach intervention on the future goals and aspirations of Irish second-level students attending schools in areas experiencing educational disadvantage. The paper uses data gathered in 2019 and 2022, from an Irish, large-scale, longitudinal study (N = 3697) of widening participation with second-level schools (N = 19) located within areas where progression to higher education is low. The paper utilises Bronfenbrenner’s ecological systems model to assess the influence of the outreach programmes on students’ future goals and aspirations. Findings show that even when controlling for a variety of individual characteristics, participating in a school-university outreach programme was associated with students having higher future goals and aspirations. In particular, students who engaged in a mentoring programme and multiple college information activities were significantly more likely to have higher scores.
PUBLISHED
Keywords: Widening participation; secondary education; outreach; mentoring; Bronfenbrenner; higher education; Inclusive Society; Higher education access; Inclusive Education; educational inequality